Discovery of a Potent and Selective TRPC5 Inhibitor, Efficacious in a Focal Segmental Glomerulosclerosis Model - Yu, Maolin (ACS Med Chem Lett, 2019)
[Image: see text] The nonselective Ca(2+)-permeable transient receptor potential (TRP) channels play important roles in diverse cellular processes, including actin remodeling and cell migration. TRP channel subfamily C, member 5 (TRPC5) helps regulate a tight balance of cytoskeletal dynamics in podocytes and is suggested to be involved in the pathogenesis of proteinuric kidney diseases, such as focal segmental glomerulosclerosis (FSGS). As such, protection of podocytes by inhibition of TRPC5 mediated Ca(2+) signaling may provide a novel therapeutic approach for the treatment of proteinuric kidney diseases. Herein, we describe the identification of a novel TRPC5 inhibitor, GFB-8438, by systematic optimization of a high-throughput screening hit, pyridazinone 1. GFB-8438 protects mouse podocytes from injury induced by protamine sulfate (PS) in vitro. It is also efficacious in a hypertensive deoxycorticosterone acetate (DOCA)-salt rat model of FSGS, significantly reducing both total protein and albumin concentrations in urine.